2019
DOI: 10.5114/jcb.2019.85903
|View full text |Cite
|
Sign up to set email alerts
|

Influence of dwell time homogeneity error weight parameter on treatment plan quality in inverse optimized HDR cervix brachytherapy using SagiPlan

Abstract: Purpose Restricting the gradients of dwell times between adjacent dwell positions can potentially be beneficial in reducing the probability of unwanted hot/cold spots occurring, if the planned applicators/anatomy relative positions change before or during treatment. This constraint, however, may degrade plan quality. This study, for the first time, aims to quantify the impact of modulation restriction on plan quality indices in inverse optimization for cervix high-dose-rate (HDR) brachytherapy usi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 27 publications
0
7
0
Order By: Relevance
“…The role of controlling neighboring dwell times in quality of treatment plan is controversial. In a recent study, a negative correlation was found between modulation restriction, and both HR-CTV D 90 and V 100 in cervix BT as well as an increasing restriction, negatively affected the conformity index [36]. According to the results of Mavroidis et al [37], dwell time regularization technique in HIPO introduced a minor improvement in the effectiveness of the optimized prostate HDR dose distributions.…”
Section: Discussionmentioning
confidence: 97%
“…The role of controlling neighboring dwell times in quality of treatment plan is controversial. In a recent study, a negative correlation was found between modulation restriction, and both HR-CTV D 90 and V 100 in cervix BT as well as an increasing restriction, negatively affected the conformity index [36]. According to the results of Mavroidis et al [37], dwell time regularization technique in HIPO introduced a minor improvement in the effectiveness of the optimized prostate HDR dose distributions.…”
Section: Discussionmentioning
confidence: 97%
“…[47] and [50] have a parameter between zero and one to control the DTMR, where zero is the least restrictive choice, and this parameter value is suggested 47 to be in the range 0.1–0.2. A DTMR is implemented in the treatment planning system SagiPlan but it is suggested 51 that the DTMR parameter should be zero, corresponding to no restriction.…”
Section: Mathematical Modelsmentioning
confidence: 99%
“…Sensitivity analysis of inverse planning parameters: Investigates whether various effective parameters (e.g., the optimization run-time) affect the quality of inverse planning routines [5,32,[60][61][62]. Selection of suitable parameters [32].…”
Section: Treatment Optimization Verificationmentioning
confidence: 99%
“…They offer DT/DW manual adjustment, graphical optimization, geometrical optimization, and inverse planning approaches, such as inverse planning by simulated annealing (IPSA) [77] and hybrid inverse treatment planning and optimization (HIPO) [78]. But before using the optimization algorithms, the physicist should evaluate these routines to ensure that they work correctly and robustly and assess the sensitivity of the resulting plans to the available parameter settings [3,11,14,15,17,18,58,62]. Also, appropriate training of users is required [5].…”
Section: Treatment Optimization Verificationmentioning
confidence: 99%